Conflict Management in Islamic Education Institutions: An Islamic Approach to Problem-Solving - Khoirul Anwar; Widyatmike Gede Mulawarman; Khalid Rahman; Sitti Anggraini; Hajer Abdallah Albshkar (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This research examines the application of conflict management based on Islamic values in Kalimasada Islamic Boarding School, Jombang. Using a qualitative approach with a case study method, the research was conducted for six months (January-June 2024) through in-depth interviews, participatory observation, and document analysis. The results showed that conflict management in this pesantren is based on Islamic principles such as justice, peace, and dialog. The mediation system involving senior santri as mediators proved to be effective in resolving conflicts. The active involvement of pesantren administrators in monitoring and managing conflicts creates an environment conducive to conflict resolution. This study also reveals that effective communication and the application of Islamic values in conflict management not only help resolve conflicts but also support the creation of a more harmonious and inclusive educational environment. The findings make a significant contribution to the development of Islamic values-based conflict management approaches in Islamic educational institutions. The results of this study are expected to be a reference for the development of conflict management systems in other Islamic educational institutions